Feasibility of a Patient-Centered Deprescribing Process to Reduce Inappropriate Use of Proton Pump Inhibitors. (January 2015) - Reeve, Emily; Andrews, Jane M.; Wiese, Michael D.; Hendrix, Ivanka; Roberts, Michael S.; Shakib, Sepehr
Background: Proton pump inhibitors (PPIs) are inappropriately prescribed in up to 50% of users. Systematic medication review and cessation of inappropriate medications or deprescribing may improve patient outcomes and reduce costs.Objective: The aim of this study was to assess the feasibility of a patient-centered deprescribing process in a population of adults with complex polypharmacy.Methods: This was a prospective feasibility study. Participants were recruited from hospital outpatient clinics. The patient-centered deprescribing process consisted of 5 steps: comprehensive medication history, identification of potentially inappropriate medications, determining if the medication can be ceased, planning the withdrawal regimen (eg, tapering where necessary), and provision of monitoring, support, and documentation. Feasibility was determined by assessing time taken to complete the different steps of the deprescribing process and participant feedback.Results: In all, 57 PPI users were recruited; participants were 70 ± 14 years old and took 14 ± 6 medications. The indication for PPI use was verified in 43 participants and judged as potentially inappropriate in 19 (44%); 8 were suitable for trial withdrawal, and 6 consented. All 6 successfully ceased (n = 3) or reduced (n = 3) their PPI use, and this was sustained at 6 months postintervention in 4 participants.Conclusions: The patient-centered deprescribing process can safely reduce inappropriate PPI prescribing in a small proportion of people. Although the process was acceptable to participants, difficulties in accessing complete medical histories, time limitations, and minimal evidence to support effectiveness in certain indications were barriers to implementation of the process in clinical practice.